Impact of rainwater harvesting on hydrological processes in a fragile watershed of South Asia - Garg, K. K.; Anantha, K. H.; Venkataradha, A.; Dixit, S.; Singh, R.; Ragab, R. (Wiley, 2021)
Agricultural water management (AWM) interventions play an important role in ensuring sustainable food production and mitigating climate risks. This study was carried out in a watershed located in a low rainfall (400–600 mm) region of western India. The Soil and Water Assessment Tool model was calibrated using surface runoff, soil loss, and reservoir storage levels, between the year 2000 and 2006. The investigation indicated that the various AWM interventions increased groundwater recharge from 30 mm/year to 80 mm/year and reduced surface runoff from 250 mm/year to 100 mm/year. The intervention structures were refilled two to three times during the monsoon season depending on rainfall intensity and duration. The interventions have the advantage of building a resilient system by enhancing groundwater availability even in dry years, stimulating crop intensification and protecting the landscape from severe erosion. The results indicate that soil erosion has been reduced by more than 75% compared to the nonintervention situation. Moreover, the AWM interventions led to the cultivation of 100–150 ha of fallow land with high-value crops (horticulture, vegetables, and fodder). Household income increased by several folds compared to the nonintervention situation. The study showed about 50% reduction in downstream water availability, which could be a major concern. However, there are a number of ecosystem trade-offs such as improved base flow to the stream and reduction in soil loss that should be considered. The study is of great importance to stakeholders to decide on the optimal design for AWM interventions to achieve sustainable development goals.